A Suite of Reduced-Order Models of a Single-Layer Lithium-Ion Pouch Cell. Issue 14 (21st October 2020) - Marquis, Scott G; Timms, Robert; Sulzer, Valentin; Please, Colin P; Chapman, S. Jon
Abstract : For many practical applications, fully coupled three-dimensional models describing the behavior of lithium-ion pouch cells are too computationally expensive. However, owing to the small aspect ratio of typical pouch cell designs, such models are well approximated by splitting the problem into a model for through-cell behavior and a model for the transverse behavior. In this paper, we combine different simplifications to through-cell and transverse models to develop a hierarchy of reduced-order pouch cell models. We give a critical numerical comparison of each of these models in both isothermal and thermal settings, and also study their performance on realistic drive cycle data. Finally, we make recommendations regarding model selection, taking into account the available computational resource and the quantities of interest in a particular study.